Wedang Dokter - Sutanta, Sutanta; Hasbi, Habid Al; Ningrum, Andriani Noerlita (Universitas Mataram, 2025)
Public health can be improved through promotional and preventive efforts utilizing local herbal plants. Metuk Village has potential crops of ginger, turmeric, lemongrass, lime, and kepok banana waste that have not been optimally managed. The